Economic development, technical change and income distribution: A conversation between Keynesians, Schumpeterians and Structuralists. Introduction to the Special Issue - Alberto Botta; Gabriel Porcile; Rafael S.M. Ribeiro (PSL Quarterly Review, 2018)
The original “manifesto” that gave rise to the Structuralist development theory was written for the Economic Commission of Latin America (ECLA, subsequently ECLAC, after incorporating the Caribbean States in 1984) by Raul Prebisch (1949). This work had a strong impact on both the theoretical and policy debates and served as a rationale for the efforts at structural change and industrialization that many developing countries adopted in the following decades. By and large, the Latin American Structuralist tradition focuses on how the external constraint disproportionately affects output growth and domestic policies in less developed economies. The existence of bottlenecks in the productive system and labor market dualism characterizing peripheral economies opens space for state intervention and industrial policies as a way to promote structural transformation and economic development.